Aortic Stiffness and the Risk of Incident Mild Cognitive Impairment and Dementia - Pase, Matthew P; Beiser, Alexa; Himali, Jayandra J; Tsao, Connie; Satizabal, Claudia L; Vasan, Ramachandran S; Seshadri, Sudha; Mitchell, Gary F (Stroke (1970), 2016)
Aortic stiffening increases the transfers of high pressure and flow pulsatility to small cerebral vessels potentially causing the accumulation of vascular brain injury. Our aim was to investigate the prospective association of aortic stiffness with the risks of incident mild cognitive impairment and dementia. We studied 1101 dementia-free Framingham Offspring study participants (mean age, 69±6 years; 54% women). Aortic stiffness was measured as carotid-femoral pulse wave velocity using applanation tonometry and modeled as a linear variable and the top 2 quintiles (>11.4 m/s). Outcomes were the 10-year risk of incident mild cognitive impairment and dementia, including clinically characterized Alzheimer disease. We observed 106, 77, and 59 events of mild cognitive impairment, all-cause dementia, and clinical Alzheimer disease, respectively. After adjustment for age and sex, higher continuous aortic stiffness predicted an increased risk of mild cognitive impairment (hazard ratio, 1.40 [95% confidence interval, 1.13-1.73]), all-cause dementia (hazard ratio, 1.45 [95% confidence interval, 1.13-1.87]), and Alzheimer disease (hazard ratio, 1.41 [95% confidence interval, 1.06-1.87]). In risk factor-adjusted statistical models, aortic stiffness remained a significant predictor of mild cognitive impairment but not incident dementia. In nondiabetic patients, the top 2 quintiles of aortic stiffness were associated with a higher risk of incident all-cause dementia across all statistical models. Aortic stiffness was an independent predictor of incident mild cognitive impairment in the whole sample and with incident dementia in nondiabetic patients. Our findings suggest aortic stiffness as a potentially modifiable risk factor for clinical cognitive impairment and dementia.